Corporate patronage and editorial independence in Latin American digital media. The case of the Google News Initiative - Crespo, Regina Aída (2024)
This paper analyzes the way in which Latin American independent or alternative digital media manage the funding they need to survive in the Internet environment, without losing their political-ideological autonomy. Regarding these issues, the case of the nine media favored by the Google News Initiative (GNI), in its 2019 and 2021 calls, is used to show, through the documentary analysis method, the relationship between the ideology and the editorial policy of the media that applied to the program and the requirements set by the technology company that chose them. The objective of this paper is to inquire if the media whose projects rely on this type of corporate patronage are capable of holding and preserving their political-ideological line, by relating to financing agents who, it seems, intend to expand their influence based on new practices of the market or its own political-ideological agenda. In this sense, this paper demonstrates that asking for the support of big techs such as Google is an important strategy for the survival of alternative media. However, in this specific case, the company proposes and hopes that the financed media will move towards the construction of a financial structure capable of generating economic autonomy, with compliance with operating criteria, procedures and standardized goals that, after all, could transform news organizations into business platforms with a remarcable comercial trend.